CRITICAL SUCCESS FACTORS FOR ENTREPRENEURIAL INTENTION AMONG FEMALE UNDERGRADUATES - Irawan , Shafira Aurora; Singh , Jugindar Singh Kartar; Suppramaniam , Subaashnii (Electronic Journal of Business and Management, 2021)
Entrepreneurs are vital for economic development, yet there is a lack of research on factors influencing the entrepreneurial intention of female undergraduates in developing countries. This study examines the impact of risk-taking propensity, proactiveness, and innovativeness on the entrepreneurial intentions of female university students in Bandung, Indonesia. Using a quantitative survey strategy and convenience sampling, data was collected from 110 respondents. The findings revealed that proactiveness and innovativeness are significant factors influencing intention. However, risk-taking did not show a significant relationship with entrepreneurial intention in this demographic. The results offer valuable insights for policymakers and educators to foster female entrepreneurship.